2016
DOI: 10.3906/tar-1501-20
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition, oxidative stability, and antioxidant properties of some Hungarian and other Persian walnut cultivars

Abstract: Ten different Persian walnut cultivars were examined for their compositional data, including eight Hungarian and two introduced varieties. Oil content and fatty acid composition were determined, as well as oxidative stability (indicated by induction time). Antioxidative capacity, total polyphenol measurements, and individual phenolic compounds were also determined. Not only dry samples but fresh and stored samples were included in this study. Large differences were found among the varieties within these parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
(9 reference statements)
3
10
0
Order By: Relevance
“…Copolovici et al determined the fatty acids composition of walnut oil and compared with the literature data. Comparing with given data, ratio of palmitic acid was low and oleic acid was high in our study, but the total ratio of MUFA, PUFA, and saturated fatty acid, they were similar with fatty acid profile of different countries such as Romania, Greece, Spain, Argentina, Poland, Portugal, and Hungary, In another study, the fatty acid ratios of bitter and sweet almond oils were stated. There were minor differences between the values.…”
Section: Resultssupporting
confidence: 87%
“…Copolovici et al determined the fatty acids composition of walnut oil and compared with the literature data. Comparing with given data, ratio of palmitic acid was low and oleic acid was high in our study, but the total ratio of MUFA, PUFA, and saturated fatty acid, they were similar with fatty acid profile of different countries such as Romania, Greece, Spain, Argentina, Poland, Portugal, and Hungary, In another study, the fatty acid ratios of bitter and sweet almond oils were stated. There were minor differences between the values.…”
Section: Resultssupporting
confidence: 87%
“…Özcan et al 2 26 determined 0.2-18.4 mg/100g α-tocopherol, 7.01-12.80 palmitic, 3.47-5.64 stearic, and 33.90-46.61 oleic acids in of Macadamia integrifolia nuts cultivated in Paraguay. These results are consistent with those reported by Bujdoso et al 24 and Kırbaşlar et al 19 , Özkan and Koyuncu 1 , Özcan et al 2 , Kafkas et al 25 and Mereles et al 26 .…”
Section: Resultssupporting
confidence: 92%
“…The cultivars showed different tendencies for antioxidative properties (antioxidative capacity, total polyphenols, phenolic compounds) of tested Hungarian and Persian walnut cultivars [Bujdosó et al 2016]. For pea there were statistically evaluated results in Hegedűsová et al [2015] where within the six observed varieties, differed by ripening, there was estimated significant difference only in case of garden pea varieties early -middle late.…”
Section: Total Polyphenol Content (Tpc)mentioning
confidence: 91%